2023
DOI: 10.1007/s00330-023-10474-w
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to participate in combination screening for lung cancer, chronic obstructive pulmonary disease and cardiovascular disease in four European countries

Carina Behr,
Hendrik Koffijberg,
Maarten IJzerman
et al.

Abstract: Objectives Lung cancer screening (LCS), using low-dose computed tomography (LDCT), can be more efficient by simultaneously screening for chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD), the Big-3 diseases. This study aimed to determine the willingness to participate in (combinations of) Big-3 screening in four European countries and the relative importance of amendable participation barriers. Methods An online cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In 2023 Behr reported that among over 1400 former smokers surveyed, 70.3% were willing to undergo screening for LC and COPD. 33 …”
Section: How Individuals View Lung Cancer Screening?mentioning
confidence: 99%
“…In 2023 Behr reported that among over 1400 former smokers surveyed, 70.3% were willing to undergo screening for LC and COPD. 33 …”
Section: How Individuals View Lung Cancer Screening?mentioning
confidence: 99%